Solution of applied one-dimensional linear boundary-value problems with automatic precision - A. V. Korovaytsev; E. A. Korovaytseva; V. A. Lomovskoy (Тонкие химические технологии)
Possible basic types of applied one-dimensional linear boundary problems in problems of chemical kinetics, structures strength, aerohydroelasticity, and wave processes in continuous media are analyzed. A uniform definition of such problems based on three-parametrical formalization is formulated. With arbitrary topology problems as an example an algorithm of boundary problems solution alternative to both discrete and differential methods is suggested. Testing the algorithm with Krylov functions as an example and the problem of describing the deformation of a shell of revolution in the vicinity of a singular point are given.